The value of blockholders shaped by moderators - Rocca, Maurizio La; Montalto, Fabiola (Journal of Business Economics and Management, 2013)
This paper investigates the role of moderators in affecting the relationship between ownership and value. The results generally reveal a positive influence of blockholders on performance, that is significantly affected by moderating factors. The link becomes negative in listed firms, as well as in family ones, and vanishes in financial constrained ones. Moreover, in case of managerial opportunism, the role of blockholders increases the positive effect of ownership on performance. Conversely, new governance reforms, improving the investors’ protection, have resized the centrality of the majority shareholder. Overall, results can be used to make recommendations on how to improve corporate and country-specific governance mechanisms.